2020
DOI: 10.1108/lm-04-2020-0075
|View full text |Cite
|
Sign up to set email alerts
|

Proliferation of social media in academic libraries: use of WhatsApp as a platform for providing library services

Abstract: PurposeThis study investigated the use of WhatsApp as the platform for providing services at Mzuzu University Library in Malawi.Design/methodology/approachThe researchers conducted in-depth semi-structured interviews with five librarians that were either working or had worked at the reference desk for a period of not less than six months. Furthermore, the researchers did a content analysis of WhatsApp posts from the two tablet computers deployed at the reference desk. Qualitative data were analysed thematicall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…This proves the necessity of integrating WhatsApp as a learning tool for all the course levels of the degree programme. Thus, irrespective of the age and the level of the students, WhatsApp can be adopted as a strategic tool in conjunction with Moodle platforms or LMS (Bouhnik and Deshen, 2014; Chaputula et al , 2020). Further, it can be used separately for student collaboration and group based activities such as discussion forums, brainstorming sessions and etc.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This proves the necessity of integrating WhatsApp as a learning tool for all the course levels of the degree programme. Thus, irrespective of the age and the level of the students, WhatsApp can be adopted as a strategic tool in conjunction with Moodle platforms or LMS (Bouhnik and Deshen, 2014; Chaputula et al , 2020). Further, it can be used separately for student collaboration and group based activities such as discussion forums, brainstorming sessions and etc.…”
Section: Discussionmentioning
confidence: 99%
“…Although it is considered a form of mobile instant messaging (Church and Oliveira, 2013; Padmavathy et al , 2018; Cruz-Cárdenas et al , 2019; Martinez-Comeche and Ruthven, 2021), it is also technically identified as a social networking application, which facilitates people wider access to information (Bouhnik and Deshen, 2014). WhatsApp provides a variety of functions, such as text messages, images, audio files, video files and links to web addresses (Church and Oliveira, 2013; Bouhnik and Deshen, 2014; Jailobaev et al , 2021) at low cost (Chaputula et al , 2020). Thus, this simple operating system allows access to people of different ages and backgrounds; a person only requires a smartphone with an active Internet connection to install the application and join WhatsApp (Bouhnik and Deshen, 2014).…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…It instigates the readers of such information, and the readers then may take unlawful actions Spreading inappropriate information quickly (SIIQ) Leung (2008), Choliz (2012), Augner and Hacker (2012), Rosenbaum and Wong (2012), Burnett and Lloyd (2020) Electronic platforms like WhatsApp, WeChat and so on have the capability to disseminate information quickly. The information so spread is found to be mostly wrong, inappropriate, and unfounded Ease of using instant messaging (EOUIM) Bandura (1997), Garret and Danziger (2008), Yi et al (2009), Sangma (2017), Gong et al (2018) Ease of use is construed as a perception by which individuals believe that some efforts are needed for learning new technology like instant messaging platforms Instant messaging is cost effective (IMCE) Zeithaml (1988), Kim and Srivastava (2007), Hamari et al (2015), Kim and Shin (2015), Chaputula et al (2020) When individual proceeds to use a new technology, the individual assumes the utility of the system by comparing what is gained against what is spent. If the latter is less, users perceive the system to be cost effective and then proceed to use it Loose regulation of instant messaging (LRIM) Hinduja (2004), Moitra (2005), Mehta and Singh (2013), Agarwal (2015), Narahari and Shah (2016), Udem et al (2020) With electronic media, an influx of information is disseminated, which might be right or wrong.…”
Section: Data Collection Strategymentioning
confidence: 99%
“…Studies reveal that IM is responsible for spreading information quickly, and these messages are sometimes unverified (Leung, 2008; Kangaspunta, 2018; Chaputula et al , 2020; Udem et al , 2020; Basile et al , 2021). Studies have shown instances where unverified messages are inflammatory (Mohit, 2012; Gong et al , 2018; Thrassou et al , 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Social media is a practical, low-cost method by which libraries can disseminate information as well as foster community engagement. Previous studies surrounding the use of social media in libraries have explored various aspects such as content (Shiri & Rathi 2013;Anderson 2015;Mon & Lee 2015;Joo et al 2018;Xie & Stevenson 2019;Joo et al 2020), stakeholder perceptions (Abidin et al 2013;Anwyll et al Winter 2013;Winn et al 2015;Cavanagh 2016;Shafawi & Hassan 2018;AlAwadhi & Al-Daihani 2019;Jones & Harvey 2019;Budu et al 2020;Pashootanizadeh & Rafie 2020;Williams et al 2021), and effective use strategies (Anwyll et al Fall 2013;Harmon & Messina 2013;Ramsey & Vecchione 2014;Smeaton & Davis 2014;Stone 2014;Valenza et al 2014;Mon 2015;Zou et al 2015;Peacemaker et al 2016;Rossmann & Young 2016;Bickford 2017;Gow 2017;Guevara 2018;Woodworth 2018;Fonseca 2019;Trucks 2019;Chaputula et al 2020). However, the majority of this literature has limited its focus to social media in the general sense or to individual platforms; thus, very little has been done to investigate and compare libraries' use of multiple platforms, particularly in-depth.…”
Section: Social Media Usage In Librariesmentioning
confidence: 99%